2016
DOI: 10.1080/09546634.2016.1180340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psoriasis activity and topical treatment on serum lipocalin-2 levels

Abstract: Lipocalin-2 might be a marker of psoriasis and convey cardiovascular or metabolic risk in psoriatic patients, but may not be a reliable indicator of inflammation, severity of psoriasis nor efficacy of antipsoriatic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…Increased irisin levels were associated with major adverse CV events in patients with established coronary artery disease after percutaneous coronary intervention. 31 In a recent study, Baran et al 32 found that serum irisin levels were insignificantly increased in psoriatic patients when compared with healthy controls ( p = 0.38). They also observed a positive statistical relation with irisin and lipocalin-2 (LCN-2).…”
Section: Discussionmentioning
confidence: 94%
“…Increased irisin levels were associated with major adverse CV events in patients with established coronary artery disease after percutaneous coronary intervention. 31 In a recent study, Baran et al 32 found that serum irisin levels were insignificantly increased in psoriatic patients when compared with healthy controls ( p = 0.38). They also observed a positive statistical relation with irisin and lipocalin-2 (LCN-2).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, there are conflicting results regarding the correlation between serum LCN2 and PASI [12, 15]. However, serum LCN2 level may not be a reliable indicator in the efficacy of antipsoriatic treatment [7, 23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been related to obesity, metabolic syndrome, and cardiovascular disease [6]. In addition, psoriasis has also been recognized as an independent risk factor for myocardial infarction, which may cause serious negative impact on the quality of life [7]. Psoriatic arthritis (PsA) is a chronic, inflammatory, and debilitating arthritis associated with psoriasis [8].…”
Section: Introductionmentioning
confidence: 99%
“…Baran et al [69] reported that serum lipocalin-2 levels were much higher in psoriatic patients than in controls, although they were not significantly related to the inflammation markers BMI or PASI. They concluded by saying that lipocalin-2 may be a good predictor of psoriasis and cardiovascular risk, but not a reliable indicator of inflammation, severity of psoriasis, or antipsoriatic treatment outcome.…”
Section: Association Between Some Obesity Biomarkers and Psoriasismentioning
confidence: 99%